Carbohydrate energy use during various interval training distances at common speeds
Interval test sets of 8 x 200 and 32 x 50 m crawlstroke swims at the same pace were compared. The 200 m repeats, in spite of the same total workload, required greater amounts of muscle glycogen. The 50 m repeats required a greater amount of anaerobic (alactacid) energy contribution. This demonstrates that despite the same pace and distance covered the energy requirements were different. The shorter distance required more alactacid energy than the greater lactacid demands of the 200 m swims. Interval sets of 100 to 400 m enhance the rates of energy use. Sets of 50 m do not place much demand on tolerance for lactic acid or metabolic waste products. Implication: Even though the pace and workload of the two sets was similar their training effects were very different. It is incorrect to equate workout sets on obvious factors such as pace and total distance. Extensive use of different sets of repetitions will alter the nutritional requirements of swimmers.